Growth performance of Nile tilapia reared in cages in a farm dam submitted to a feed reduction strategy in a periphyton-based system - David, Luiz H. [UNESP]; Campos, Denis WJ. [UNESP]; Pinho, Sara M. [UNESP]; Romera, Daiane M.; Garcia, Fabiana [UNESP] (Hindawi, 2022)
The periphyton-based system is a low-cost and sustainable strategy for small-scale producers who have limited technology and budgets. This study aimed to evaluate the effects of different feed restriction levels (50% and 67%), using periphyton as a natural food source, on the growth performance of Nile tilapia reared under real culture conditions in cages placed in a farm dam. Three treatments were tested: F100—fish fed daily only on feed; F50—fish fed every other day, plus periphyton; and F33—fish fed every two days, plus periphyton. Considering the results of fish growth in F50 and F33 compared with F100 and the low amount of periphyton dry matter, it is reasonable to state that the fish under feed restriction did not take advantage of the periphyton due to its low availability. This low availability of the periphyton is possibly associated with the water N:P ratio and its variation over the experimental period. Therefore, periphyton-based systems are not indicated for conditions with a low N:P ratio or subject to great variations in this ratio.